Glucose - 6 - phosphate dehydrogenase deficiency In a group of Iraqi children - Abbas, Sawsan S. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: Glucose -6- phosphate deosphate dehydnogenase (G6PD) deficiency is a common problem in Iraqi as well as in tropical A subtropical region. Aim of study: to study the epidemiological aspect of G6PD deftaiency among Iraqi children. Patients & Methods: This cross sectional study was conducted in the Pediatric ward/A L Kadhiymia Teaching Hospital during the season of Fava beans ingestion. Patients who were presented with acute attack of pallor were collected , history was taken and physical examination was done. Results : Ninety seven cases were studied, males were affected more than female with a ratio of 3.85:1, the peak of age was between ( 1 - 5years ), 76 cases ,(78.36%).Previous history of neonatal jaundice was found in 24 cases (24.74%), the acute hemolytic attack was precipitated by Fava beans ingestion in all of the cases ( !()()%) and pallor was the main presenting feature in all of them. The attack was very severe in 43 cases (44.32 %) with arrange of PCI’ between ( 1-9 %). History of recurrence was encountered in I 1 cases ( 11.34 %), family history of G6PD deficiency was found in 22 cases ( 22.68%) .G6PD level was estimated two months later in 31 cases (31.95 %) only and were found to be deficient.